The undrained bearing capacity of strip footings under eccentric loading: effect of soil-footing interface tensile strength. Issue 2 (17th February 2020) - Khitas, Nour El Houda; Benmeddour, Djamel; Mellas, Mekki; Mabrouki, Abdelhak
Abstract: In order to satisfy the exceptional conditions imposed by the offshore structures, a particular attention should be paid to the stability of shallow foundations resting on purely cohesive soil. One important specification of the offshore foundations is their soil-footing interface which can sustain tension. This paper studies the effect of the tensile strength of this interface on the undrained bearing capacity of a strip footing and assesses the reliability of the effective width method under eccentric loading. This is done by a numerical modelling using the finite difference method. Failure envelopes, failure mechanisms and normal stress distribution at the interface are presented and compared with available results from literature. The results show that the effective width method is not reliable in the presence of the tensile strength at the interface. This strength yields supplementary stability and keeps the footing in contact with the soil even under low vertical loading.